2023
DOI: 10.1002/jgh3.12870
|View full text |Cite
|
Sign up to set email alerts
|

Daikenchuto significantly improves stool consistency and lower gastrointestinal symptoms in patients with chronic constipation

Abstract: Background and Aim: A number of basic and clinical studies have confirmed that the traditional Japanese herbal medicine, Daikenchutou (DKT) has a pharmacological effect on cholinergic and serotonergic mechanisms with a favorable safety profile and an improving effect on lower gastrointestinal (GI) symptoms including abdominal pain or bloating. The purpose of this study is to evaluate the efficacy and safety of DKT on chronic constipation. Methods: This multicenter, randomized, placebo-controlled, double-blinde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Although Kampo medicines are used in clinical practice, there are few reports with a high level of evidence, such as RCTs, to prove their effectiveness. Recently, Manabe et al randomized 63 patients with chronic constipation (including constipated IBS) who met the ROME III criteria to receive Daikenchuto or placebo and treated them for four weeks (74). They reported that the overall improvement was significantly higher in the Daikenchuto group than in the placebo group, and Daikenchuto also significantly improved stool consistency and abdominal distension compared with the placebo group.…”
Section: Probiotics Prokinetics and Kampo Medicinementioning
confidence: 99%
“…Although Kampo medicines are used in clinical practice, there are few reports with a high level of evidence, such as RCTs, to prove their effectiveness. Recently, Manabe et al randomized 63 patients with chronic constipation (including constipated IBS) who met the ROME III criteria to receive Daikenchuto or placebo and treated them for four weeks (74). They reported that the overall improvement was significantly higher in the Daikenchuto group than in the placebo group, and Daikenchuto also significantly improved stool consistency and abdominal distension compared with the placebo group.…”
Section: Probiotics Prokinetics and Kampo Medicinementioning
confidence: 99%
“…3 It was included by the State in the "Catalogue of Ancient Classical Prescriptions (First Batch)" and has been extensively compiled in medical texts throughout the ages. 4 For the treatment of digestive system illnesses such as postoperative ileus (POI), [5][6][7] small intestinal mucositis, 8 chronic constipation, 9 and colitis, 2 DJZD is frequently used as a basic formula and has a long history of clinical application. Modern pharmacological studies have verified that DJZD possesses anti-inflammatory 2 and analgesic, 10 as well as promotes the motor function of the gastrointestinal tract 11 and anti-gastrointestinal tumours.…”
Section: Introductionmentioning
confidence: 99%